2011 IEEE International Conference on Advanced Information Networking and Applications 2011
DOI: 10.1109/aina.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MAC on Localization in Large-Scale Seabed Sensor Networks

Abstract: There are many technical challenges to realize the myriad of applications envisaged for underwater acoustic sensor networks (UASNs); in particular, determining the location of each node or localization. While various schemes have been proposed recently, the impact of MAC protocols for localization has not been studied. A MAC protocol that can enable many sensor nodes in large-scale networks to share the limited channel resource is an indispensable component to maximize localization coverage and speed, while mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An example of a closed form solution is the Bancroft method [2]. However the set of equations can also be solved iteratively using NewtonRaphson, Levenberg-Marquadt and many more methods of iterative optimization [6].…”
Section: Position Estimation and Time-synchronizationmentioning
confidence: 99%
“…An example of a closed form solution is the Bancroft method [2]. However the set of equations can also be solved iteratively using NewtonRaphson, Levenberg-Marquadt and many more methods of iterative optimization [6].…”
Section: Position Estimation and Time-synchronizationmentioning
confidence: 99%
“…Kim et al [18] evaluate the impact of the MAC on localization in a large-scale UASN. They show that the performance of a simple MAC protocol, namely carrier sense multiple access (CSMA), is better than T-Lohi [10] (a recently designed underwater MAC protocol).…”
Section: Introductionmentioning
confidence: 99%
“…An existing medium access control (MAC) protocol may be used for packet exchanging [14]; however, there is no guarantee that it will perform satisfactorily for the localization task. The performance of localization under different MAC protocols is evaluated in [15], where it is shown that a simple carrier sense multiple access (CSMA) protocol performs better than the recently introduced underwater MAC protocols such as T-Lohi [16].…”
Section: Introductionmentioning
confidence: 99%